SERVANT LEADERSHIP SEBAGAI STRATEGI MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN - NURJANAH, RIFQOH; ASY'ARI, HASYIM (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2024)
To achieve the quality of educational services that is in line with national standards, school principals must implement an approach. School principals are expected to be able to achieve educational goals in an effective and efficient manner. Being able to encourage the organization's human resources, teaching staff, school employees and students to complete their respective responsibilities is a form of school principal leadership. To move parts of the organization, an approach is needed that is appropriate to the education system, namely the helper leader style. This study was conducted using a qualitative approach. The research was conducted through interviews with school principals as respondents, and the results were adjusted to theoretical analysis from literature data. Data reduction techniques, such as analyze, select, and discard, support the veracity of this data. The research results show that there are six servant leadership models, namely: Value people, develop people, build community, display authentic, provide leadership, and share leadership. And the characteristics of servant leadership: listening, fulfilling, empathy, healing, self-awareness, persuasion and conceptualization. ABSTRAKUntuk mencapai kualitas layanan pendidikan yang sesuai dengan taraf nasional, kepala sekolah harus menerapkan pendekatan. Kepala sekolah diharapkan dapat mencapai tujuan pendidikan dengan cara yang efektif dan efisien. Mampu mendorong sumber daya manusia organisasi tenaga pendidik, karyawan sekolah, dan siswa untuk menyelesaikan tanggung jawabnya masing-masing adalah bentuk kepemimpinan kepala sekolah. Untuk menggerakkan bagian-bagian organisasi, diperlukan pendekatan yang sesuai dengan sistem pendidikan, yaitu gaya pemimpin pembantu. Studi ini dilakukan menggunakan pendekatan kualitatif. Penelitian dilakukan melalui wawancara dengan kepala sekolah sebagai responden, dan hasilnya disesuaikan dengan analisis teori dari data kepustakaan. Teknik reduksi data, seperti menganalisis, memilih, dan membuang, mendukung kebenaran data ini. Hasil penelitian menunjukan bahwa terdapat enam model servant leadership yaitu: Value people, develop people, build community, display authentic, provide leadership, dan share leadership. Dan karakteristik servant leadership: mendengarkan, memenuhi, empati, penyembuhan, kesadaran diri, persuasi dan konseptualisasi.